THE IMPACT OF THE PRINCIPAL’S LEADERSHIP ON TEACHERS’ PERFORMANCE AT SD IT INSAN GEMILANG - Yulia Ratna; Sagaf, S. Pettalongi; Masmur M (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aimed to analyze the impact of principal leadership on teachers’ performance at SD IT Insan Gemilang. The study used a quantitative approach with an ex post facto method. The research population consisted of all teachers actively teaching at SD IT Insan Gemilang, and the entire population were used as the sample through a saturated sampling technique. Data were collected by using a questionnaire developed based on indicators of principal leadership and teachers’ performance. The data were analyzed using descriptive statistics and simple linear regression to test the influence between variables. The results showed that principal leadership has a positive and significant effect on teachers’ performance. Effective leadership, characterized by the ability to provide motivation and direction and to create a conducive work environment, Effective leadership enhances teachers' job satisfaction in performing their duties. These findings suggested that strengthening principal leadership is a key strategy for improving teacher’s performance.